A Defined Antigen Skin Test That Enables Implementation of BCG Vaccination for Control of Bovine Tuberculosis: Proof of Concept - Srinivasan, Sreenidhi; Subramanian, Saraswathi; Shankar Balakrishnan, Sai; Ramaiyan Selvaraju, Kathiravan; Manomohan, Vandana; Selladurai, Suganya; Jothivelu, Monika; Kandasamy, Srinivasan; Gopal, Dhinakar Raj; Kathaperumal, Kumanan; Conlan, Andrew J. K.; Veerasami, Maroudam; et al. (Frontiers in Veterinary Science, 2020)
In most low- and middle-income countries (LMICs), bovine tuberculosis (bTB) remains endemic due to the absence of control programs. This is because successful bTB control and eradication programs have relied on test-and-slaughter strategies that are socioeconomically unfeasible in LMICs. While Bacillus Calmette-Guérin (BCG) vaccine-induced protection for cattle has long been documented in experimental and field trials, its use in control programs has been precluded by the inability to differentiate BCG-vaccinated from naturally infected animals using the OIE-prescribed purified protein derivative (PPD)-based tuberculin skin tests. In the current study, the diagnostic specificity and capability for differentiating infected from vaccinated animals (DIVA) of a novel defined antigen skin test (DST) in BCG-vaccinated (Bos taurus ssp. taurus x B. t. ssp. indicus) calves was compared with the performance of traditional PPD-tuberculin in both the skin test and in vitro interferon-gamma release assay (IGRA). The IFN- production from whole blood cells stimulated with both PPDs increased significantly from the 0-week baseline levels, while DST induced no measurable IFN- production in BCG-vaccinated calves. None of the 15 BCG-vaccinated calves were reactive with the DST skin test (100% specificity; one-tailed lower 95% CI: 82). In contrast, 10 of 15 BCG-vaccinated calves were classified as reactors with the PPD-based single intradermal test (SIT) (specificity in vaccinated animals = 33%; 95% CI: 12, 62). Taken together, the results provide strong evidence that the DST is highly specific and enables DIVA capability in both skin and IGRA assay format, thereby enabling the implementation of BCG-vaccine based bTB control, particularly in settings where test and slaughter remains unfeasible.